2015
DOI: 10.2320/matertrans.m2014304
|View full text |Cite
|
Sign up to set email alerts
|

Damping Capacities of Ti<sub>50</sub>Ni<sub>50&minus;</sub><i><sub>x</sub></i>Cu<i><sub>x</sub></i> Shape Memory Alloys Measured under Temperature, Strain, and Frequency Sweeps

Abstract: The damping capacities of Ti 50 Ni 50¹x Cu x SMAs with x = 0³20 at% were measured by DMA under temperature, strain and frequency sweep tests. The tan ¤ value exhibited at B2¼B19 transformation is significantly higher than that at B2¼B19A transformation under temperature/strain sweep tests. In the strain sweep test, the tan ¤ value decreases as the frequency increases, but it increases as the applied strain increases. The tan ¤ curves of the strain sweep tests can be fitted by tan ¤ = K¾ n with n values being c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although the tan δ values in this study are most contributed from the transitory term (IF Tr ), as mentioned in Section 2.1, but from the strain sweep tests [17], we found that the phase transformation term (IF PT ) and the intrinsic term (IF I ) associated with B2↔B19 transformation are also higher than those associated with B2↔B19’ transformation. The magnitude of the tan δ value exhibited by IF PT term and that by IF I term are closely related to the mobility of the phase interface between the parent phase and martensite and the twin boundary between the martensite variants.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the tan δ values in this study are most contributed from the transitory term (IF Tr ), as mentioned in Section 2.1, but from the strain sweep tests [17], we found that the phase transformation term (IF PT ) and the intrinsic term (IF I ) associated with B2↔B19 transformation are also higher than those associated with B2↔B19’ transformation. The magnitude of the tan δ value exhibited by IF PT term and that by IF I term are closely related to the mobility of the phase interface between the parent phase and martensite and the twin boundary between the martensite variants.…”
Section: Resultsmentioning
confidence: 60%
“…Here, M S ’and M S are the starting transformation temperatures of B2→B19 and B19→B19’, respectively. The DSC curves for x = 7.5 at.% SMA also show only a B2↔B19’ peak in cooling and heating [17]. Obviously, the DMA curves for x = 7.5 at.% SMA, as shown in Figure 1c, cannot be used to distinguish the B19 martensite from B2↔B19’ transformation, as revealed in ρ and DSC tests.…”
Section: Resultsmentioning
confidence: 99%